The Effect of Abietic Acid (Cedrus Deodara Compound) on the Histopathology of Rat Stomach in Comparison with Ulcer Healing Drugs (Medical Forum Monthly, 2024)
Purpose of study: The aim of this study is to observe the anti-ulcer effects of Abietic acid (a compound of Cedrus deodara) on the histopathology of rat’s stomach in comparison with standard anti-ulcer drugs such as Femotidine (H2 receptor blocker) and Protonix (a proton pump inhibitor). Design of study: Experimental study. Place and Duration of Study: This study was conducted in the department of Pharmacology, Institute of Pharmaceutical Sciences, Baqai Medical University, Karachi. Materials and Methods: This study was carried out on 50 albino rats of Wistar Strain for experimental purpose. The animals were divided into five groups and each group comprised of 10 rats (i.e. 5 male and 5 female). The experimental procedure was repeated for three times. The compound of abietic acid was provided by the chemistry department of Karachi University. The ulcer was induced in the animals by giving 1ml of 100% ethanol after 48 hrs of fasting. The induction of ulcer in animal was then treated with abietic acid (25 mg/kg for 2 weeks) orally through feeding tube. The ulcer healing effects of this compound were then compared with the effect of known anti-ulcer drugs. Results: Abietic acid used in this study showed the healing effects on the mucosal epithelium of stomach, decreased inflammatory cells and formation of granulation tissues on the sub mucosal layer during histopathological examination. Conclusion: It is thus concluded that abietic acid has an anti-ulcerative effects when given in the required dose and may be adapted in the management of gastrointestinal disorders particularly in peptic ulcer.